Married 'til Monday - Hunter, Denise, 1968- (A Chapel Springs romance, 2015)
"With a big anniversary party in the works for her parents, Ryan will pretend to be Abby's husband for just one last weekend. Ryan McKinley has tried to move on from his ex-wife, Abby. He's sulked, he's gotten angry, and ultimately he bought her dream house. Big mistake. Living alone in the massive 2-story has only made him miss her more. When her parents call him out of the blue about their anniversary party in Summer Harbor, Maine, Ryan believes God has dropped a golden opportunity straight in his lap. Abby McKinley never exactly told her parents about the divorce. A strained relationship with her dad has culminated in a distant relationship with her parents, but she's finally succumbed to her mom's pressure to make the drive for their 35th-anniversary party. Then Ryan shows up on her doorstep, looking as devastatingly handsome as ever. When he insists he's going to Seabrook, with or without her, Abby knows she can't say no. Her parents still think they're married and now Ryan knows it too. Besides, he only wants to check in with his best friend from college -- her cousin Beau, who just lost his dad. It's just a one-week road-trip with the man who broke her heart. What could possibly go wrong?"--